2012
DOI: 10.1177/0730888412465879
|View full text |Cite
|
Sign up to set email alerts
|

From the Shop Floor to the Kitchen Floor

Abstract: Using data from the Panel Study of Income Dynamics we explore the relationship between current and early maternal occupational complexity and preadolescent children's academic achievement in mathematics and reading. We measure white-collar occupational complexity with an index that incorporates task complexity, authority, and autonomy. Blue-collar occupational complexity is observed with a measure of task complexity with things. Controlling for differential selection into employment, we find that current mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
(79 reference statements)
1
6
0
Order By: Relevance
“…Findings revealed that, for both mothers and fathers, reports of greater job autonomy across the child’s first year of life predicted less overreactive parenting and more involved parenting that, in turn, predicted greater adaptive skills and fewer behavior problems for children. Consistent with the work of Kohn (1977), Parcel and Menaghan (1994), and Yetis-Bayraktar, Budig, and Tomaskovic-Devey (2013), our data suggest that parents’ workplace environment is related to parenting styles, which in turn affect children. Thus, working-class parents who have the opportunity to experience self-direction and autonomy on the job are more likely to transmit those same values to their children at home through more sensitive and involved parenting.…”
Section: From Research To Applicationsupporting
confidence: 88%
“…Findings revealed that, for both mothers and fathers, reports of greater job autonomy across the child’s first year of life predicted less overreactive parenting and more involved parenting that, in turn, predicted greater adaptive skills and fewer behavior problems for children. Consistent with the work of Kohn (1977), Parcel and Menaghan (1994), and Yetis-Bayraktar, Budig, and Tomaskovic-Devey (2013), our data suggest that parents’ workplace environment is related to parenting styles, which in turn affect children. Thus, working-class parents who have the opportunity to experience self-direction and autonomy on the job are more likely to transmit those same values to their children at home through more sensitive and involved parenting.…”
Section: From Research To Applicationsupporting
confidence: 88%
“…In addition, parents' working conditions are associated with not only their own but also their family members' health (Parcel & Menaghan, 1994;Vandell & Ramanan, 1992;Yetis-Bayraktar et al, 2013). In a review of the relevant research www.ccsenet.org/gjhs Global Journal of Health Science Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies have demonstrated a direct, significant association between working conditions and the health status of family members, including children (Parcel & Menaghan, 1994;Vandell & Ramanan, 1992;Yetis-Bayraktar, Budig, & Tomaskovic-Devey, 2013). Parents' poor socioeconomic status, including employment, may affect children's health and development, which is an important health factor over the course of the entire lifetime and potentially influences both childhood and adulthood (Ruijsbroek et al, 2011).…”
mentioning
confidence: 99%
“…For example, Melvin Kohn and colleagues’ seminal work showed that what people experience in their jobs translates into value orientations and behaviours that they apply outside their workplace, for example parenting (Kohn and Schooler, 1982). Occupational characteristics such as maternal occupational complexity (task complexity, authority and autonomy) influence parental skills and value orientations, affecting their parenting styles and children’s cognitive outcomes and academic achievement (Parcel and Menaghan, 1994; Yetis-Bayraktar et al, 2013). Hook et al (2021) also found that occupational autonomy was positively associated with mothers’ time in interactive care.…”
Section: Introductionmentioning
confidence: 99%